Pengaruh Kemudahan dan Manfaat BSI Mobile Banking terhadap Kepuasan Mahasiswa Jurusan Perbankan Syariah Angkatan 2020 UIN Bukittinggi - Aisyah Zalmi Putri; Dewi Manda Anggraini (Journal of Management and Creative Business, 2024)
The main objective of this research is to find out how the benefits and convenience of BSI Mobile Banking affect students majoring in sharia banking at UIN Bukittinggi in 2020. The method used in this research is a quantitative method. Forty respondents were selected through the use of purposive sampling selection techniques because not all samples met the appropriate criteria for the phenomenon under investigation. Methods such as hypothesis testing, classical assumption testing, basic linear regression testing, and instrument testing are used for data analysis. Based on data analysis carried out using SPSS version 25, the Adjusted R-Square test produces a value of 0.765. This shows that 76.5% of the impact on student satisfaction is caused by the convenience and benefits of BSI Mobile Banking, while the rest is influenced by other variables. Based on the T test, it is known that the convenience variable has a calculated T value greater than the T table value (1.367 > 1.687, 0.000 < 0.05), while the benefit variable has a calculated T value greater than the T table value (4.552 > 1.667, 0.000 > 0, 05), resulting in Ho rejection. It can be concluded that students' enjoyment of BSI Mobile Banking transactions is significantly influenced by the ease and benefits of using this service, or Ha received. Therefore, it is natural that sharia banking students Class of 2020 at UIN Bukittinggi will be more satisfied with BSI Mobile Banking if they feel an increased level of comfort and benefits in using this service.